Approaches to Instructional Leadership: Organizational Influences in Contexts of (Mis)match. Issue 4 (July 2021) - Jimerson, Jo Beth; Quebec Fuentes, Sarah
Instructional leadership efforts are complicated when leaders and teachers do not share areas of expertise. Leaders work to bridge this divide through a number of approaches, such as collaboration with specialist personnel and the development of leadership content knowledge (LCK). The purpose of this study was to explore the organizational factors that help shape the ways school leaders enact instructional leadership when supervising in areas of (mis)match. Interviews with n = 31 teachers and school leaders indicated that organizational factors influenced the ways in which leaders understood and enacted their roles related to instructional supervision. Evidence also suggested the presence of organizational structures that could be reframed as robust, intentional supports to help school leaders develop LCK.